Evolución del Modelo Premo para determinar las Emociones de Marca Basada en las Percepciones - Cedillo Jurado, Tatiana (2016)
The investigation analyzes the methodology named Emotion Circles. It is used as tool in the emotional branding to determine the emotions that certain brands produces based on perceptions and the interaction between the product with the senses auditory -visual, tactile and smell.It comes from components of the Model Premo de Pieter Desmet, which identifies the emotions taking as a reference what is perceived. The case analyzed is Dove, across the tactile and olfactory interaction with the natural soap, and audio-visual soap by means of the interaction with video about of the campaign Royal Beauty.There was used the method of direct observation in focal groups, the inductive method across surveys and interviews; thatallowed to determine the positioning of the brand in his market segment. Other results turn on the emotions that it produces, being the most relevant: surprise, joy and hope.